Gulliver's travels : part : I-IV - Swift, Jonathan; Swift, Jonathan, 1667-1745.; Reeves, James (Morristown, N.J. : Silver Burdett Co., 1984)
A simplified, abridged version of Gulliver's experiences with the little people of Lilliput.
Keywords: Fantasy